The Protos Mandate: Science Fiction and Neoliberalism - Alfaro Vargas, Roy (2016)
The relation between science fiction and neoliberalism is analyzed through the study of the novel The Protos Mandate, by Nick Kanas. The concept of novum explains certain changes present in the novel, in relation to the tradition linked to the poetics of science fiction developed by Darko Suvin and to the idea of the dialectics between the context of writing/production and the diegetic context of the literary (or film) text, to understand the reasons for the changes happened in the so-called current neoliberal science fiction.